Collaborations Workshop 2018 (CW18) Report – Culture Change, Productivity and Sustainability - Raniere Gaia Costa da Silva; Shoaib Sufi; Selina Aragon Camarasa (Research Ideas and Outcomes, 2019)
The Collaborations Workshop 2018 (CW18) took place at The School of Mathematics, Cardiff University from the 26th to 28th March 2018. 90 people attended the event to discuss the themes of the workshop: culture change, productivity and sustainability. With a mix of lightning talks, keynotes, Q&A panels, discussions with speed blogging, collaborative ideas sessions, mini-workshops & demos, a social programme and a Hack Day in the agenda, CW18 was a feature-packed and immersive event.